2008
DOI: 10.1177/0269881108092126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute alcohol consumption and alcohol expectancy on processing of perceptual cues of emotional expression

Abstract: We recently demonstrated that alcohol elicits a difference between men and women in perceptual threshold for facial expressions of sadness. However, this study did not include a manipulation of alcohol expectancy. Therefore, we sought to determine whether these effects may be due to the expectation of having consumed alcohol. Male and female participants (n = 100) were randomised using a balanced-placebo design to receive either an alcoholic or a non-alcoholic drink and to be told that this was alcoholic or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(111 citation statements)
references
References 14 publications
(17 reference statements)
4
103
4
Order By: Relevance
“…In the present study, a relatively low amount of alcoholic beer (0.25-0.3 g/kg alcohol) reduced the time to recognize happy faces compared with non-alcoholic beer but did not alter the speed of affect recognition of other basic emotions or recognition accuracy. Happy faces were also better recognized after a low dose of alcohol (0.14 g/kg) in another study (Kano et al 2003), but we did not replicate the impairments in recognition of sad faces after alcohol (0.4 g/kg) administration that were reported in several other studies (Attwood and Munafo 2014;Craig et al 2009) or after administration of the prosocial drug MDMA using the same face emotion task . Alcohol had no effect on the recognition of disgust in the present study, similar to the effects of low doses of alcohol in other studies, whereas no effects or an increase in the recognition of disgust were reported after high doses of alcohol (0.5-0.8 g/kg; Felisberti and Terry 2015;Kamboj et al 2013).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In the present study, a relatively low amount of alcoholic beer (0.25-0.3 g/kg alcohol) reduced the time to recognize happy faces compared with non-alcoholic beer but did not alter the speed of affect recognition of other basic emotions or recognition accuracy. Happy faces were also better recognized after a low dose of alcohol (0.14 g/kg) in another study (Kano et al 2003), but we did not replicate the impairments in recognition of sad faces after alcohol (0.4 g/kg) administration that were reported in several other studies (Attwood and Munafo 2014;Craig et al 2009) or after administration of the prosocial drug MDMA using the same face emotion task . Alcohol had no effect on the recognition of disgust in the present study, similar to the effects of low doses of alcohol in other studies, whereas no effects or an increase in the recognition of disgust were reported after high doses of alcohol (0.5-0.8 g/kg; Felisberti and Terry 2015;Kamboj et al 2013).…”
Section: Discussioncontrasting
confidence: 90%
“…Indeed, face emotion recognition can be experimentally influenced by acute alcohol administration. Specifically, alcohol (0.2-0.4 g/kg) was shown to impair the recognition of sad but not happy or angry facial expressions in social drinkers (Attwood and Munafo 2014;Attwood et al 2009b;Craig et al 2009). Better discrimination of happy faces at a low dose (0.14 g/kg) compared with a high dose (0.56 g/kg) of alcohol was also reported (Kano et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, there are results that suggest beneficial effects of alcohol on cognition [53] which is the case of the study carried out by Britton, Singh-Manoux and Marmot [54]. These authors investigated the relationship between alcohol consumption and cognitive function (they assessed memory, verbal and mathematician reasoning, recognition and understanding of semantic fluency words and phonemic awareness) and they concluded that for middle-aged individuals, alcohol improves some cognition aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Although no effects were observed for angry facial stimuli, impairment in the recognition of sad facial expressions may nevertheless indirectly augment aggressive behaviour, as sad facial expressions can act to inhibit aggression in others (Eisenberg et al 1989;Miller and Eisenberg 1988). This selective effect of alcohol on perceptual threshold for sad emotional expressions was replicated in a more recent study using a balanced-placebo design, although no sex differences were observed (Craig et al 2008).…”
Section: Introductionmentioning
confidence: 85%